Biological One‐Way Functions for Secure Key Generation. Issue 2 (5th December 2018) - Dodda, Akhil; Wali, Akshay; Wu, Yang; Pannone, Andrew; Reddy, Likhith Kumar; Raha, Arnab; Ozdemir, Sahin Kaya; Ozbolat, Ibrahim Tarik; Das, Saptarshi
Abstract: Disorder is fundamental to nature and natural phenomena, providing countless information sources, which are astronomically difficult to duplicate, but have yet to be exploited for cryptographic applications. While the contemporary crypto systems, relying on the premise of abstract mathematical one‐way functions, are relatively difficult to decipher with reasonable and/or finite resources, the situation is bound to change with the advent of quantum computers, necessitating physically unclonable entropy sources. As such, inspiration is drawn from the disorder that is prevalent in nature and inherent to biological systems for designing disruptive mechanisms for cryptographic key generation. It is demonstrated that the spatiotemporal dynamics of an ensemble of living organisms such as T cells can be used for maximum entropy, high‐density, and high‐speed key generation. Further, such biology based one‐way functions are oblivious to any mathematical representations and are computationally expensive to decipher even if an adversary has an exhaustive knowledge of the key generation mechanisms, which include cell type, cell density, key sampling rate, and sampling instance. The introduction of such biological one‐way functions can greatly enhance the ability to protect information in the post quantum era. Abstract : By exploiting the natural disorders inherent to biological species, a disruptive cryptography system is enabled for the generation of true random numbers that are near‐ideal in entropy, practically unclonable, and astronomically difficult to decipher even with exhaustive knowledge of the system. The introduction of such biological one‐way functions enhance the ability to protect information in the era of increasing globalization.